The Interfacial Lipid Binding Site on the Potassium Channel KcsA Is Specific for Anionic Phospholipids - Marius, Phedra (Biophysical Society, 2005)
Lipid binding to the potassium channel KcsA from Streptomyces lividans has been studied using quenching of the fluorescence of Trp residues by brominated phospholipids. It is shown that binding of phospholipids to nonannular lipid binding sites on KcsA, located one each at the four protein-protein interfaces in the tetrameric structure, is specific for anionic phospholipids, zwitterionic phosphatidylcholine being unable to bind at the sites. The binding constant for phosphatidylglycerol of 3.0 ± 0.7 mol fraction(−1) means that in a membrane containing ∼20 mol% phosphatidylglycerol, as in the Escherichia coli inner membrane, the nonannular sites will be ∼37% occupied by phosphatidylglycerol. The binding constant for phosphatidic acid is similar to that for phosphatidylglycerol but binding constants for phosphatidylserine and cardiolipin are about double those for phosphatidylglycerol. Binding to annular sites around the circumference of the KcsA tetramer are different on the extracellular and intracellular faces of the membrane. On the extracellular face of the membrane the binding constants for anionic lipids are similar to those for phosphatidylcholine, the lack of specificity being consistent with the lack of any marked clusters of charged residues on KcsA close to the membrane on the extracellular side. In contrast, binding to annular sites on the intracellular side of the membrane shows a distinct structural specificity, with binding of phosphatidic acid and phosphatidylglycerol being stronger than binding of phosphatidylcholine, whereas binding constants for phosphatidylserine and cardiolipin are similar to that for phosphatidylcholine. It is suggested that this pattern of binding follows from the pattern of charge distribution on KcsA on the intracellular side of the membrane.